Studies on commercial policy and economic growth - Islam, Nurul; The Pakistan Institute of Development Economics (Pakistan : The Pakistan Institute of Development Economics, 1970)
This volume is intended to fill the lacunae in the field of economic literature for Pakistan
includes appendixex
ijb, 17/01/2019
Loans
Keywords: Economic history; Commercial policy; Pakistan